Unappreciated Depreciation: Connecting The Line of “What Counts” and “How to Count” Company’s Sustainable Assets - Putu Yunartha Pradnyana Putra; Made Pramana Putra; I Putu Sriartha (Jurnal Ilmiah Akuntansi dan Humanika, 2023)
Little is known about the phenomenon of depreciation charged from both economic and accounting point of view. This article addresses the lack of discussion related to depreciation charged, which is currently an important factor in determining the company's performance. Based on financial report data published by public manufacturing companies in Indonesia, we estimate that an aggressive and consistent depreciation charged will be appreciated by investors in the capital market. In addition to the important role in determining the company's performance, we observe that depreciation charged has an equal position with other operating costs. Finally, we identify that depreciation charged can be viewed as an early perceived loss for investors and others.